Sintesis dan Karakterisasi Spinel Zinc Ferrite (ZnFe2O4) Menggunakan Metode Kopresipitasi - Aprilia Melisa; Gifran Noval Rahmadoni; Rahmatul Husna; Sarah Rodiatul (Indonesian Journal of Chemical Connections, 2023)
This research focuses on the synthesis and characterization of spinel zinc ferrite (ZnFe2O4) using coprecipitation method. The study examines the structural, morphological, and magnetic properties of the synthesized materials. The results indicate that coprecipitation method produces ZnFe2O4 nanoparticles with uniform size distribution and good crystallinity.